IMPLEMENTASI PERATURAN REKTOR UNIVERSITAS SEBELAS MARET NOMOR 6 TAHUN 2018 TENTANG PENYUSUTAN ARSIP PENELITIAN TAHUN 2021 - Yani Maryudiasti; Aris Tri Haryanto; Winarti . (Master of Public Administration, Universitas Slamet Riyadi, 2022)
This study aims to describe and analyze the implementation of the Rector’s UNSRegulation Number 6 of 2018 concerning Archive Disposition at UNS in the 2021Research Year and the factors that support and hinder its implementation. ThisRector’s UNS Regulation regulates the disposal of archives at Universitas SebelasMaret by reducing the volume of archives through the transfer of inactivearchives, destruction of archives that have no use value, and submission of staticarchives. This research is a qualitative descriptive study. The data were obtainedfrom the results of interviews, observations, and document searches. Sampleswere taken by purposive sampling technique. The data analysis was carried outqualitatively using an interactive data analysis model, testing the validity withdata triangulation techniques. The results of the research on the bureaucraticstructure, namely the Unit Kearsipan II has not been formed, there are alreadySOPs and there is no fragmentation. The communication factor, the indicator isthe clarity or clarity of the transmission receiver and the consistency of thecommunication transmission has been fulfilled. Resource factors, the indicatorsare the skills of implementing activities that need to be improved and lack offocus, as well as inadequate facilities to carry out activities. The last factor thatinfluences is the tendency of the implementer, the indicator is the perception of theimplementer who is very supportive of carrying out archive disposition.Keywords: implementation, archive disposition, archives.